Analisis Pendidikan Sebagai Suatu Sistem: Analisis Komponen, Dinamika, Dan Tujuan Dalam Perspektif Kontemporer - Jon Roi Tua Purba; Asister Fernando Siagian; Natalina Purba; Binur Panjaitan; Mangasi Malatua (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
Education is a multidimensional process that cannot be understood in parts but must be viewed as a holistic, interconnected system. A systems approach to education is becoming increasingly relevant in the contemporary context characterized by globalization, the development of digital technology, and the demands of 21st-century competencies. This article aims to analyze education as a system by examining the main components of education, the dynamics of interactions between components, and educational objectives from a contemporary perspective. The research method used is library research, analyzing various sources of literature, including books, scientific journal articles, and national and international education policy documents. The results of the study indicate that the education system consists of input, process, output, and outcome components that influence each other and cannot be separated. The dynamics of the education system require adaptive, collaborative management, and a focus on quality and relevance. Understanding education as a system is expected to serve as a conceptual foundation for the formulation of sustainable education policies and practices.